The importance of algae in the national economy - R.N.Mominova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Livestock, pillage, farming, poultry farming, and others. the role of green water grass-chlorella in the development of a number of succulents I large. The article highlights the great importance of green water grass - chlorella in the national economy. It also indicates its distribution and chemical composition, and methods of use.